Rho-Kinase II Inhibitory Potential of Eurycoma longifolia New Isolate for the Management of Erectile Dysfunction. (15th May 2019) - Ezzat, Shahira M.; Okba, Mona M.; Ezzat, Marwa I.; Aborehab, Nora M.; Mohamed, Shanaz O.
Abstract : Background. Eurycoma longifolia Jack (Fam.: Simaroubaceae), known as Tongkat Ali (TA), has been known as a symbol of virility and sexual power. The aim of the study was to screen E. longifolia aqueous extract (AE) and isolates for ROCK-II inhibition. Results. The AE (1-10 μ g/ml) showed a significant inhibition for ROCK-II activity (62.8-81%) at P < 0.001 with an IC50 (651.1 ± 32.9 ng/ml) compared to Y-27632 ([(+)-( R )- trans -4-(1-aminoethyl)- N -(4-pyridyl)cyclohexanecarboxamide dihydrochloride]) (68.15-89.9 %) at same concentrations with an IC50 (192 ± 8.37 ng/ml). Chromatographic purification of the aqueous extract (AE) allowed the isolation of eight compounds; stigmasterolT1, trans- coniferyl aldehydeT2, scopoletinT3, eurycomalactoneT4, 6 α - hydroxyeurycomalactoneT5, eurycomanoneT6, eurycomanolT7, and eurycomanol-2- O - β -D-glucopyranosideT8 . This is the first report for the isolation ofT1 andT3 from E. longifolia and for the isolation ofT2 from genus Eurycoma . The isolates (at 10 μ g/ml) exhibited maximum inhibition % of ROCK-II 82.1 ± 0.63 (T2), 78.3 ± 0.38 (T6), 77.1 ± 0.11 (T3), 76.2 ± 3.53 (T4), 74.5 ± 1.27 (T5), 74.1 ± 2.97 (T7), 71.4 ± 2.54 (T8), and 60.3 ± 0.14 (T1), where the newly isolated compound trans- coniferyl aldehydeT2 showed the highest inhibitory activity among the tested isolated compounds and even higher than the total extract AE. The standard Y-27632 (10 μ g/ml) showed 89.9 ± 0.42 % inhibition for ROCK-II activity when compared to control at P < 0.0001. Conclusion. The traditional use of E. longifolia as aphrodisiac and for male sexual disorders might be in part due to the ROCK-II inhibitory potential.